(3GdeYHb HTQM Sde GdefWbs - (3EHQGgje Hf eMeO GdJGOdi GdQTGWis; (3YHO GdQMef Hf eMeO GdUZjQ GdGNVQj, CHh RjO,J (B983 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ GHQGgje Hf eMeO GdJGOdi GdQTGWi s
(3BNQgG (B:s
(3hYOOgG GKfG YTQ GdMed hGdKhQ hGdLhRGA hGdSQWGf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs